Measuring the environmental awareness by using Schahn scale in its third amended "issue on a sample of Tishreen University students" - Chrebah, Bouchra; Kahila, Reem; BouBou, Mounzer (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of current research is to measuring the environmental awareness of Tishreen University students, by using the "Environmental Awareness Scale" which had been prepared by "Schahn" in its amended third form (1999) after being standardized on the Syrian environment. The research aimed to identify the differences in the degrees of environmental awareness among members of the research sample according to each of the following variables: Faculty type (theoretical-practical), gender (males-females), and the academic year. This research was conducted on a sample of (850) students (males-females) in the University of Tishreen to extract the psychometric properties of the scale and to check the significance of validity and reliability. The researchers used arbitrators' sincerity, honesty, and internal consistency to verify the veracity of scale's statements. Reliability was verified through consistency and repeated reliability, by using Cronbach's Alpha equation by split-half. The results found out that the values of honesty and reliability coefficients were high and statistically significant and demonstrated the validity of the scale. It was also showed there were statistically significant differences in the level of environmental awareness among male and female students. While no clear differences were shown among students that were related to the college type and school year variables.